Treatment method - LIM REBECCA; WALLACE EUAN (2022)
The present disclosure generally relates to methods of treating mammalian subjects by enhanced cell-based therapeutic methods to promote tissue and neuronal repair, regeneration and/or repair. The disclosure also encompasses a medicament for treating a mammalian subject and a method of producing the medicament wherein the composition comprises exosomes derived from allogeneic mammalian amniotic epithelial cells from a donor mammal of the same species. 本公开一般涉及通过增强的基于细胞的治疗方法来治疗哺乳动物受试者从而促进组织和神经元修复、再生和/或修缮的方法。本公开还涵盖了用于治疗哺乳动物受试者的药物和所述药物的生产方法，其中组合物包括源自同种异体哺乳动物羊膜上皮细胞的外泌体，所述同种异体哺乳动物羊膜上皮细胞来自同一物种的供体哺乳动物。